Life as we knew it / 1. - Pfeffer, Susan Beth, 1948- (Life as We Knew It, 2008)
Through journal entries sixteen-year-old Miranda describes her family's struggle to survive after a meteor hits the moon, causing worldwide tsunamis, earthquakes, and volcanic eruptions.